Ergo-Iconical Value Positioning Strategy to Improve Pharmaceutical Company Performance - Purnomo, Bogi; Andriyansah, Andriyansah (ProBisnis : Jurnal Manajemen, 2024)
The pharmaceutical distribution industry in Indonesia is currently growing rapidly with the increasing number of Large Pharmaceutical Companies (PBF), both state-owned companies, private companies and foreign companies that acquire private companies. The number of large pharmaceutical companies in Indonesia according to BPOM data in 2018 is 2,232 PBFs. This makes competition and competition tighter to get distribution appointments from drug principals or manufacturers and to become distribution companies that become market leaders. Another impetus is the increasingly tight distribution margin pressure caused by the government's lower pricing for BPJS products so that drug principals or manufacturers reduce distribution fees to distributors and there is competition for lower distribution fees. Some of these factors make large pharmaceutical companies must be able to manage company operations properly and have a competitive advantage in order to survive and become the distributor of choice for principals and customers. Currently, there are quite a number of large pharmaceutical companies that cannot withstand the pressure of the distribution fee margin and have resulted in the pharmaceutical company going out of business.